2019
DOI: 10.1002/jac5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dalbavancin on length of stay in acute bacterial skin and skin structure infections

Abstract: Purpose Acute bacterial skin and skin structure infections (ABSSSI) are common reasons for hospital admission. A pathway to shift care to the outpatient setting sooner could decrease length of stay (LOS). Our not‐for‐profit community health system has developed a novel practice of partnering with hospitalists as part of a multidisciplinary early discharge of hospitalized patients with dalbavancin for ABSSSI. The primary purpose of this study was to evaluate outcomes associated with this process. Methods This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The increased risk of side effects and lack of alternate treatment options lend to the ID PharmD being able to determine potential dalbavancin candidates and assist with transitions of care [ 27 ]. The impact of the ID PharmD has been shown in the previous study, as they are able to assist with clinical knowledge skills to aid in selecting, counseling, and effectively treating this patient population with dalbavancin [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased risk of side effects and lack of alternate treatment options lend to the ID PharmD being able to determine potential dalbavancin candidates and assist with transitions of care [ 27 ]. The impact of the ID PharmD has been shown in the previous study, as they are able to assist with clinical knowledge skills to aid in selecting, counseling, and effectively treating this patient population with dalbavancin [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional study in Germany demonstrated the cost-savings effect of dalbavancin in MRSA ABSSSI by reducing LOS by 6.45 days with a cost savings of $3099.69 (2865 €) [ 16 ]. The previous study at our institution was associated with decreased cost and length of stay [ 10 ]. The impact of vial replacement was shown to mirror previous data of dalbavancin as a cost-effective option in the self-pay population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations